Outcome of the patients who underwent minimally invasive screw fixation for calcaneal fracture: an institutional study - Patel, Vivek Amritbhai; Vala, Pathik (International Journal of Research in Orthopaedics, 2019)
Background: Calcaneal fractures account for 2% of all fractures with approximately 65-75% intra-articular. The aim of the present study is to determine the outcome of the patients who underwent minimally invasive screw fixation for calcaneal fracture in our institute. Methods: The present study was performed in 31 patients who underwent closed reduction and fixations with screw in this institute for the duration of 2 years were included in this study. Present study was conducted to determine the functional outcome of patients with calcaneal fractures treated with minimally invasive fixation of fractures with cancellous screws after indirect reduction with JESS or manual reduction or with Steinmen pin. Results: The average age of the patients was 44.14 years, ranging from 16 to 74 years, 28 patients were males and 3 were female. The AOFAS score at last follow up was 78.05 this improvement was also significant statistically (p<0.05). The mean Bohler angle at the last radiographic evaluation was 32.87°. The complications noted were proud implant with superficial wound infection in one, deep infection in 2 patients and delay in wound healing in 2 patients, persistent pedal edema in 2 patients. Conclusions: ORIF of calcaneal fractures is associated with high skin complications and comorbidities. Percutaneous screw fixation has fewer skin complications and can have satisfactory functional outcome. JESS or similar external fixator can be used intraoperatively for achieving reduction through ligamentotaxis.